Diagnostic Imaging and Management of Common Intra-articular and Peri-articular Soft Tissue Tumors and Tumorlike Conditions of the Knee - Evenski, Andrea J.; Stensby, James Derek; Rosas, Samuel; Emory, Cynthia L. (The Journal of Knee Surgery, 2019)
Intra-articular (IA) and peri-articular (PA) tumors of the knee are frequently encountered by orthopaedic surgeons. Nonetheless, due to the possibility of great morbidity and potential mortality, it is important to recognize and differentiate between benign and malignant lesions in a timely manner. Therefore, the purpose of this article is to provide a concise, practical, and updated review of commonly encountered IA and PA tumors including intratendinous gout, synovial chondromatosis, schwannoma, pigmented villonodular synovitis, and synovial sarcoma, and a detailed description of differentiating features to include various imaging modalities.
Keywords: musculoskeletal oncology; intra-articular; tumor; review; orthopaedics